Application of 3M (Drawing, Tear, Pasting) to Improve Artistic Ability in Children Aged 5-6 Years - Suharni, Suharni; Br. Hasibuan, Humaidah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The background of this research is the lack of children's ability to use media related to 3m activities. The purpose of this study was to see children's artistic abilities in 3m activities, namely drawing, tearing, and pasting. The method used in this study is a qualitative approach method. Methods of data collection by conducting interviews, observation, and documentation. Based on the results of research regarding the application of 3m activities to improve artistic abilities in children aged 5-6 years at PAUD Bunda Streat Gurilla No 23, Medan Perjuangan District, Medan City, which was carried out for one month experienced a good improvement. The results of the increase in children's artistic abilities that occur can be seen in the change in attitude during learning takes place. In the early stages of learning, children show reluctance or hesitation during activities, so over the learning period, children begin to feel comfortable and begin to be confident in showing the works of art made by children. It can also be seen that, when applying 3M, children are categorized as quite good at drawing according to the teacher's instructions, drawing lines with five fingers, tearing paper, and gluing pieces of paper according to the drawing pattern.